IFPRI and Bangladesh: A strong partnership for food security and nutrition - International Food Policy Research Institute (International Food Policy Research Institute, 2019)
IFPRI’s wide range of partnerships in Bangladesh have influenced the design and operation of large-scale national programs and provided real-time policy analysis during times of crisis. The country’s commitment to using research to guide policy decisions has helped to foster a culture of evaluation that can truly have an impact on hunger and malnutrition. IFPRI’s decades of research in Bangladesh are set against the context of longstanding partnerships with the government and national research organizations.